Observation of Age‐Related Decline in the Performance of the Transverse Abdominis Muscle. Issue 1 (10th June 2015) - Davies, Paul; Grace, Fergal M.; Lewis, Mark P.; Sculthorpe, Nicholas
Abstract: Background: Previous research has shown that the performance of skeletal muscle declines with advancing age. Coordination of the transverse abdominis (TrA), a deep postural muscle, has been shown to be reduced in persons with low back pain. No previous research has studied the effect of age on the activation on this muscle. Objective: To assess the effect of age on TrA activation in response to rapid arm abduction. Design: Cross‐sectional cohort study. Setting: University exercise physiology laboratory. Participants: A total of 18 adult men (aged 27 ± 7.0 years) for the younger group and 11 older adults (5 men and 6 women, aged 59.6 ± 4.0 years) were recruited for this study. Method: Participants were positioned on a treatment table and performed a series of rapid arm abduction movements with their right arm while the activation of the TrA muscle was recorded using ultrasound imaging. Onset of arm abduction was measured using surface electromyography and synchronized with the ultrasound through the ultrasound unit's electrocardiogram channel. The mean time difference between the 2 events was calculated during post‐hoc analysis. Main Outcome Measurements: A Mann‐Whitney test was performed to test for differences in the onset performance of the TrA muscle between the 2 groups. Results: Results showed that the older group was significantly slower than the younger group in engaging their TrA in response to the rapid arm abduction ( P = .036). A separate analysis of the older group data showed that no significant differences existed between the male and female participants that could potentially have acted as a confounding factor for the main finding ( P = .126). Conclusions: This study shows that older adults were slower than younger adults in activating their TrA muscle in response to rapid arm abduction. This delay has the potential to lead to increased occasions when the low back is unprotected, increasing the likelihood of injury or low back pain.